(untitled) (Cuadernos de Extensión Universitaria de la UNLPam, 2020)
For those of us who have been going through the pu-blic university for decades, a clear tendency in most of our institutions to rethink their senses, their missions, their functions, in sum: their must be. In these times and these contexts in which deep inequalities are made visible with absolute clarity, these tendencies to construct new meanings acquire a particular relevance. We understand that public universities in the exercise of their autonomy and as members of the State, must assume a leading role with a contribution that contributes to guaranteeing rights, in particular, of the subalternized sectors. This critical positioning is inescapable to consolidate the social commitment of our higher education institutios. This compelling transformative intention has a valuable background. In this sense, we warn that both in Argentina and in some of the countries of the Region, tendencies to consolidate, systematize, institutionalize processes of emancipatory articulation in their relations with the territory, organizations and social movements have been reproduced for some years, many of them, through curricularization processes in its different meanings. These experiences, dissimilar by the way, find the need to settle, to institutionalize themselves through various conformations that in some cases converge in Educational Social Practices or similar names, with different, unique formats, but with different meanings as well. That is why we propose to display, analyze, make visible some of the salient characteristics of these processes, the regulations, their singularities, similarities, the multiplicity of their feelings, in sum, their metaphors.